Combined heterozygosity of FLT3ITD, TET2, and DNMT3A results in aggressive leukemia - Baskar Ramdas; Palam Lakshmi Reddy; Raghuveer Singh Mali; Santhosh Kumar Pasupuleti; Ji Zhang; Mark R. Kelley; Sophie Paczesny; Chi Zhang; Reuben Kapur (JCI Insight, 2022)
Heterozygous mutations in FLT3ITD, TET2, and DNMT3A are associated with hematologic malignancies in humans. In patients, cooccurrence of mutations in FLT3ITD combined with TET2 (TF) or FLT3ITD combined with DNMT3A (DF) are frequent. However, in some rare complex acute myeloid leukemia (AML), all 3 mutations cooccur — i.e., FLT3ITD, TET2, and DNMT3A (TFD). Whether the presence of these mutations in combination result in quantitative or qualitative differences in disease manifestation has not been investigated. We generated mice expressing heterozygous Flt3ITD and concomitant for either heterozygous loss of Tet2 (TF) or Dnmt3a (DF) or both (TFD). TF and DF mice did not induce disease early on, in spite of similar changes in gene expression; during the same time frame, an aggressive form of transplantable leukemia was observed in TFD mice, which was mostly associated with quantitative but not qualitative differences in gene expression relative to TF or DF mice. The gene expression signature of TFD mice showed remarkable similarity to the human TFD gene signature at the single-cell RNA level. Importantly, TFD-driven AML responded to a combination of drugs that target Flt3ITD, inflammation, and methylation in a mouse model, as well as in a PDX model of AML bearing 3 mutations.